Isolated splenic abscess due to melioidosis in type 1 diabetes mellitus: laboratory diagnosis of Burkholderia pseudomallei in resource-restricted setting. Issue 2 (4th February 2021) - Gupta, Abhishek Prakash; Halder, Ratan; Chakraborty, Mandira; Chakraborty, Partha Pratim
Abstract : Diabetes mellitus, type 1 in particular, is a well-recognised risk factor for melioidosis, a disease caused by Burkholderia pseudomallei . Melioidosis is endemic in Southeast Asia and in northern Australia and has a variety of clinical presentation, isolated splenic abscess being one of them. B. pseudomallei, however, is an uncommon aetiology of splenic abscess. The diagnosis of melioidosis is often overlooked unless the clinician and the microbiologist are suspicious of the condition. Multiple splenic abscesses and perisplenic collection were noted in CT scan of the abdomen in a patient of type 1 diabetes, presenting with fever for preceding 4 weeks. B. pseudomallei was isolated from the splenic aspirate and the diagnosis was made based on gram stain and routine biochemical tests. He was successfully treated with antibiotics. We postulate that the likely route of infection was inoculation through skin, the integrity of which was compromised by multiple subcutaneous insulin injections.